FACTORS THAT INFLUENCE TRUANCY IN SELECTED SECONDARY SCHOOLS - PUNIT KUMAR JHA (International Journal of Multidisciplinary Research and Studies, 2020)
Students who willfully skip one or more of their scheduled classes are engaging in the delinquent behaviour known as truancy, which is increasingly recognised as a changing and emerging problem. Around the world, truancy is viewed as a cankerworm that eats away at the foundations of educational programmes, which has resulted in a variety of challenges and roadblocks for secondary school students as they progress through their educational career (Adeyemi, 2011; Animasahun, 2007). Any absence from obligatory schooling that is both unplanned and purposeful, as well as unauthorised and criminal, is termed truancy. It might also apply to kids who are present in school but who do not participate in any of their lessons. Truancy is defined as a pattern of behaviour characterised by inconsistent or nonexistent school attendance. It is also considered a delinquent and antisocial behaviour (Animasahun, 2009). Truancy is an academic delinquent, social and law execution concern. Absenteeism in school by children and teenagers lowers their chances of reaching their educational potential (Siziya, Muula, & Rudatsikira, 2007). According to Kee (2001), truancy is defined as the deliberate, premeditated, and planned absence of students from educational institutions without the approval of their parents or without a valid explanation or justification. According to Rothman (2001), who attempts to define truancy, "truancy is an act of remaining away from school without leave." Chukwuka (2013) describes truancy in a similar manner, stating that it is "absence from school for no justifiable cause." Adekunle (2015), in a discussion on the topic of truancy, notes that truancy entails an individual willfully absenting themselves from school without the agreement of the school, as well as leaving and fleeing specified instructional hours without authorization.